Development of NO3 - N Analyser for Real-Time Nitrate Control in a Pilot Urban Wastewater Treatment Plant - Casares, M. (2007)
This paper reports on the design and con- struction of a prototype for the measurement of Nitrate-Nitrogen (NO− − N) concentration in urban wastewater for real-time nitrate control in treatment plants. The system acquires the sample in an automatic mode and performs the measurement using an ion selective electrode (ISE). Additionaly the equipment has a friendly user interface and can exchange data with a supervisory system, using the MODBUS protocol over a RS-485 interface.